2009
DOI: 10.4049/jimmunol.0901436
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorothioate-Modified TLR9 Ligands Protect Cancer Cells against TRAIL-Induced Apoptosis

Abstract: Hypomethylated CpG oligodeoxynucleotides (CpG ODNs) target TLR9 expressed by immune cells and are currently being evaluated as adjuvants in clinical trials. However, TLR signaling can promote some tumor growth and immune evasion, such as in multiple myeloma (MM). Therefore, deciphering the effects of CpG ODNs on cancer cells will help in preventing these adverse effects and in designing future clinical trials. TLR activation induces multiple signaling pathways, notably NF-κB that has been involved in the resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Recently, CpG-ODN with a PTO backbone was shown to protect cancer cells from TRAIL-induced apoptosis by inhibiting binding of TRAIL to its receptor (54). Further, we have, in this study, shown that CpG-ODN with a PTO-backbone prevents BMP-induced apoptosis of malignant plasma cells, and BMP-induced osteoblastogenesis by inhibiting Smad signaling in a TLR9-independent manner.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, CpG-ODN with a PTO backbone was shown to protect cancer cells from TRAIL-induced apoptosis by inhibiting binding of TRAIL to its receptor (54). Further, we have, in this study, shown that CpG-ODN with a PTO-backbone prevents BMP-induced apoptosis of malignant plasma cells, and BMP-induced osteoblastogenesis by inhibiting Smad signaling in a TLR9-independent manner.…”
Section: Discussionsupporting
confidence: 56%
“…However, in contrast to TNF-a receptors, both TRAIL receptors induce cell death. TRAIL differentially binds to TRAIL-R as illustrated by the phosphorotioate-modified CpG nucleotides, which block the binding of TRAIL to DR5 but not to DR4 and similarly bind to lexatumumab and not to mapatumumab (40). TRAIL mutants with selective binding to DR4 or DR5 also showed that binding of TRAIL to DR4 and DR5 involves different amino acids (41).…”
Section: Discussionmentioning
confidence: 99%
“…Inverse association was seen with the vascular density suggesting that possible tumor-promoting properties of TLR9 expression are not linked to induction of angiogenesis. Activation of tumor cell TLRs has been reported to promote tumor cell proliferation and resistance to apoptosis [12,31] . In this study, the TLR9 expression showed no association with tumor cell proliferation or apoptosis.…”
Section: Discussionmentioning
confidence: 99%